Coral Symbiosis Carbon Flow: A Numerical Model Study Spanning Cellular to Ecosystem Levels - Xu, Yi; Zhang, Jing; Huang, Hui; Yuan, Xiangcheng; Zhang, Junxiao; Ge, Jianzhong (Frontiers in Marine Science, 2022)
Corals rely on a symbiotic relationship with algae (zooxanthellae), which reside in the host tissue and play a critical role for host metabolism through photosynthesis, respiration, carbon translocation, and calcification. These processes affect coral reefs on different scales from cellular to organismal and ecosystem levels. A process-based dynamic model was developed and coupled with a one-dimensional (1-D) biogeochemical model to describe coral photosynthesis, respiration, and carbon translocation at the cellular level; calcification and ion transport in different coral polyp components (e.g., coelenteron, calcifying fluid) at the organismal level; and the exchange of material between corals and the ambient seawater at the ecosystem level. Major processes controlling the carbon budget in internal symbiosis were identified. For the symbiont, photosynthesis is the primary carbon source and translocation to the host is the major sink. For the host, most of the carbon translocated from the symbiont are lost through mucus leakage. In the host dissolved inorganic carbon (DIC) pool, most of the carbon is obtained from the surrounding seawater through uptake; photosynthesis and calcification are the major sinks of DIC. Based on series of scenario studies, the model produced increase of photosynthesis rate with decline of calcification rate under higher air pCO2 and associated carbonate chemistry variabilities in different polyp components. The model results support the hypothesis that elevated pCO2 stimulates photosynthesis, resulting in a reduced supply of DIC to calcification. Such coupled models allow the exploration of process-based mechanisms, complementing laboratory and field studies.